Integrating Padlet as a Digital Learning Platform in Teaching Analytical Exposition Writing to Tenth Graders - Zuhrun Nafis; Fauziyatun Ni'mah; Happy Kusuma Wardani (APPLICATION: Applied science in Learning Research, 2026)
The integration of digital platforms in EFL writing instruction requires effective implementation to support students’ writing processes. This study aimed to investigate the implementation of Padlet in teaching Analytical Exposition writing to tenth-grade EFL students and to explore students’ perceptions of its use. The study employed a descriptive qualitative approach, using classroom observation as the primary data source and a questionnaire to triangulate the data. The observations revealed that Padlet was implemented through structured instructional design, scaffolded writing stages, and collaborative peer feedback activities. The platform supported a process-based writing approach by enabling students to develop ideas gradually, revise drafts in response to feedback, and engage actively in collaborative learning. The questionnaire results confirmed that students perceived Padlet positively in terms of ease of use, learning support, collaboration and interaction, motivation and interest, perceived impact on writing ability, and overall satisfaction. The findings indicate that Padlet effectively supports the teaching of Analytical Exposition writing when integrated with clear guidance and collaborative practices. This study concludes that Padlet is a suitable digital learning platform for EFL writing instruction at the senior high school level